2006
DOI: 10.1242/jeb.02492
|View full text |Cite
|
Sign up to set email alerts
|

Delayed development and lifespan extension as features of metabolic lifestyle alteration inC. elegansunder dietary restriction

Abstract: SUMMARY Studies of the model organism Caenorhabditis elegans have almost exclusively utilized growth on a bacterial diet. Such culturing presents a challenge to automation of experimentation and introduces bacterial metabolism as a secondary concern in drug and environmental toxicology studies. Axenic cultivation of C. elegans can avoid these problems, yet past work suggests that axenic growth is unhealthy for C. elegans. Here we employ a chemically defined liquid medium to culture C. elegans an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
110
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(130 citation statements)
references
References 49 publications
13
110
3
Order By: Relevance
“…One interesting possibility is that the properties of the collagenrich cuticle, which encases the growing cells and tissues of the worm, give rise to an upper worm size limit, providing a mechanosensory cue for moulting. Consistent with this, at each moult the cuticular sheath is about the same length regardless of growth temperature [44]. In M. sexta, tracheal size limits oxygen intake due to its saltational growth, thus contributing to the requirement for moulting [16].…”
Section: Discussionsupporting
confidence: 56%
“…One interesting possibility is that the properties of the collagenrich cuticle, which encases the growing cells and tissues of the worm, give rise to an upper worm size limit, providing a mechanosensory cue for moulting. Consistent with this, at each moult the cuticular sheath is about the same length regardless of growth temperature [44]. In M. sexta, tracheal size limits oxygen intake due to its saltational growth, thus contributing to the requirement for moulting [16].…”
Section: Discussionsupporting
confidence: 56%
“…A commonly studied stress is dietary restriction, which can slow down/arrest development and reduce sexual behaviour 12,55 . In contrast to dietary restriction, where nutrients are limited, the synthetic CeMM food contains the basic nutrients in excess.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to dietary restriction, where nutrients are limited, the synthetic CeMM food contains the basic nutrients in excess. However, since others have reported that C. elegans superficially responds to CeMM similarly to dietary restriction 12 , the stress that the animal experiences might be related to the suboptimal presentation of the nutrients and the low efficiency of nutrient utilization. Although the population growth is slower in CeMM compared with a bacterial diet 10 , the population will eventually grow to high density.…”
Section: Discussionmentioning
confidence: 99%
“…So far, however, studies in C. elegans have almost exclusively utilized feeding regimes in which animals are kept on agar plates with an E. coli lawn. Metabolism of supplied nutrients or nonnutritional components by the bacteria and production of mainly unknown metabolites that might contribute to the biological effects of a dietary ingredient is a concern [33]. The use of liquid axenic media on the other hand produce phenotypic changes in development, fecundity, lifespan and metabolism when compared to the apparent ''gold standard'' of feeding bacteria [10,33].…”
Section: Discussionmentioning
confidence: 99%